Вплив графіту на фізико-механічні характеристики та трибологічні властивості вторинного поліетилену - Деркач, О. Д.; Макаренко, Д. О.; Муранов, Є. С.; Derkach, O.; Makarenko, D.; Muranov, Ye. (ЦНТУ, 2022)
Встановлено, що введення графіту в кількості 2 мас. %, в структуру вторинного поліетилену, провокує зростання напруження міцності та величини відносного видовження при розриві, на 7,7 % та 19,9 % відповідно. Виявлено, що введення графіту в структуру вторинного поліетилену призводить до підвищення мікротвердості отриманих матеріалів. Встановлено, що вторинний поліетилен, наповнений 2 % мас. графітом, забезпечує працездатність в режимі тертя без мащення за критерієм PV ≤ 0,5 МПа м/с. The purpose of the work is to study the influence of graphite on the physical and mechanical characteristics and tribological properties of secondary polyethylene. For this, a study of the physical and mechanical characteristics and tribological properties of the original secondary polyethylene on PCM based on it was carried out. The influence of the concentration of graphite in secondary polyethylene on the value of strength stress and relative elongation under tension at the maximum load and destruction of the samples was determined. It was established that the optimal concentration of graphite should not exceed 2 wt. %. An increase in the volume of the filler in the matrix leads to a significant decrease in the physical and mechanical characteristics of the obtained materials. It was established that the introduction of graphite into the structure of secondary polyethylene, regardless of its volume, leads to an increase in the microhardness of the obtained PCM. It was found that the temperature in the vicinity of friction, under the condition of friction without lubrication on steel 45 and the selected modes, did not exceed 69 ºС. An increase in linear speed above 0.5 m/s or pressure above 1 MPa leads to an increase in the temperature in the friction zone to 72...73 ºС, which is critical for polyethylene and leads to catastrophic wear of the samples. It was established that under the selected modes of friction, linear speed of sliding and pressure do not have a significant effect on the amount of wear and tear. The resulting polymer composite provides performance under the condition that the pressure does not exceed 1 MPa, and the linear speed is up to 0.5 m/s. For use in mechanisms and machines that work in friction conditions according to the criterion PV ≤ 0.5 MPa · m/s, it is possible to recommend the introduction of 2% by mass. graphite into the structure of secondary polyethylene. The introduction of graphite in the amount of up to 2% by mass. will allow to stabilize and moderately increase the strength characteristics of the obtained material, in comparison with unfilled polyethylene.
The Effect of Graphite on the Physical and Mechanical Characteristics and tribological Properties of Secondary Polyethylene
Keywords: вторинний поліетилен; графіт; фізико-механічні характеристики; трибологічні властивості; величина зноcу; secondary polyethylene; graphite; physical and mechanical characteristics; tribological properties; wear